Dual-Energy X-Ray Absorptiometry Body Composition in NCAA Division I Athletes: Exploration of Mass Distribution - Sanfilippo, Jennifer (Sports Health, 2019)
BACKGROUND: Body composition assessment is frequently used in sports medicine and athletic performance environments to assess change in response to strength training and nutrition programs. However, to effectively do so requires knowledge regarding expected body composition values relative to sport and sex. Dual-energy x-ray absorptiometry (DXA) is widely used to evaluate body composition, although its utility in relationship to specific sports, performance, or rehabilitation is not clearly defined. HYPOTHESIS: Body composition metrics and distribution of National Collegiate Athletic Association Division I collegiate athletes will vary based on sport and sex. LEVEL OF EVIDENCE: Level 4. STUDY DESIGN: Cross-sectional study. METHODS: A convenience sample of 337 athletes (229 men and 108 women) participating in football, wrestling, soccer, hockey, basketball, golf, softball, or volleyball was evaluated. DXA-measured total body composition, including bone mineral density (BMD), % lean mass, % fat, and regional distribution, were compared by sex, sport, and with an age-matched National Health and Nutrition Examination Survey (NHANES) population. RESULTS: Men had higher BMD, lower % fat (16.4% vs 25.2%) and higher % lean mass (79.2% vs 70.6%) (P < 0.001). Regional composition varied by sport and sex, with women having a greater proportion of lean mass at the trunk and men in their arms (P < 0.0001). Leg lean mass was distributed similarly between sexes (35%). Overall, the normative group (NHANES) had lower BMD and higher percentage fat. CONCLUSION: DXA-measured body composition and lean mass distribution varies by sport and sex in Division I athletes. The observed difference to the NHANES population emphasizes challenges in identifying appropriate comparison populations, reinforcing the need to compare athletes with their own baseline. CLINICAL RELEVANCE: These findings establish a framework to investigate the relevance of these variances and determine the utility of body composition analysis in elite athletes.